Comparison of the immune effects of the Chlamydia abortus MOMP antigen displayed in different parts of bacterial ghosts - Zhang, Huaiyu; Li, Zhaocai; Li, Wei; Jin, Youshun; Li, Yunhui; Xiao, Qian; Tong, Dewen; Zhou, Jizhang (Frontiers in Microbiology, 2024)
Bacterial ghosts (BGs) are promising vaccine platforms owing to their high adjuvant properties and delivery efficiency. Heterologous antigens can be anchored to different parts of BGs using genetic engineering strategies to prepare vaccines. However, several key issues need to be resolved, including the efficient preparation of BGs and determining the optimal anchoring position of exogenous antigens in the BGs. Here, we prepared an efficient temperature-controlled lysis system using lysis gene E of phage PhiX174 and used the major outer membrane protein (MOMP) of Chlamydia abortus (C. abortus) as a model antigen to explore the optimal display location of exogenous antigens in BGs. We demonstrated that the constructed recombinant temperature-controlled lysis plasmid can still stably inhibit E gene expression at 37°C, and the lysis efficiency of E. coli can reach above 99.9%. Four recombinant MOMP Escherichia coli (E. coli) ghost vaccines were constructed using different anchor sequences. These vaccines all induced strong specific antibody responses and secrete high levels of IFN-γ in immunized mice and significantly increased the clearance of C. abortus in a mouse infection model. Notably, the strongest immune effect was observed when MOMP was displayed on the surface of E. coli ghosts (rECG-InpN-M), which resulted in the clearance of C. abortus in mice 6 days earlier than that with the recombinant MOMP vaccine. Altogether, we constructed an efficient BG temperature-controlled lysis system and provided a feasible strategy for developing a BG delivery platform with enhanced immune effects.